2012
DOI: 10.3126/njms.v1i2.6604
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in type 2 diabetes mellitus patients using NCEP/ATP III and IDF criteria in Nepal

Abstract: Background: With increasing trends towards sedentary life style, obesity, diabetes mellitus, hypertension, and dyslipidaemia, the prevalence of metabolic syndrome (MetS) is rising in our country. In view of importance of diagnosis of MetS in day to day medical practice for early institution of life style therapies to reduce the atherosclerotic cardiovascular disease risk in susceptible population like in diabetes mellitus, this study has been undertaken to study the prevalence of metabolic syndrome in Nepalese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
6
8
2
1
Order By: Relevance
“…The 69.8% prevalence of MetS in our Chinese community-based patients with type 2 diabetes mellitus was very close to those reported in South Indian (73.3%) and Nepalese (71%) type 2 diabetic patients21,22. In agreement with the present results, Vyssoulis et al 11.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 69.8% prevalence of MetS in our Chinese community-based patients with type 2 diabetes mellitus was very close to those reported in South Indian (73.3%) and Nepalese (71%) type 2 diabetic patients21,22. In agreement with the present results, Vyssoulis et al 11.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we investi- gated the association between UACR below the microalbuminuria threshold and MetS in community-based patients with type 2 diabetes. The 69.8% prevalence of MetS in our Chinese communitybased patients with type 2 diabetes mellitus was very close to those reported in South Indian (73.3%) and Nepalese (71%) type 2 diabetic patients 21,22 . In agreement with the present results, Vyssoulis et al 11 and Oh et al 23 also showed that elevated urine albumin excretion within the normal range can reflect an increasing prevalence of MetS in patients with essential hypertension and in the healthy Korean men, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Our research found prevalence of 76.3% and 61.9% in male and female respectively, showing a higher prevalence in male while the research conducted by Bhattarai S et al showed higher prevalence in female with prevalence of male and female of 72% and 91% respectively [11].…”
Section: Discussioncontrasting
confidence: 45%
“…Study done by Bhattarai S et al in 2012 showed that 71% diabetic patients had metabolic syndrome with prevalence of male and female of 72% and 91% respectively [11]. The study conducted in Manipal Teaching Hospital had the prevalence of 73.9% according to NCEP ATP III with 80.3%, 69.9% and 66.8% according to Harmonized, WHO and IDF definition respectively [12].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown prevalence of overweight and obesity in certain sections of the population to be as high as 32.9% and 7.2%, respectively.18In a hospital based cross sectional study, the prevalence of metabolic syndrome in diabetes patients as per NCEP/ATP III and IDF criteria were 71% and 82%, respectively. 19 The global diabetes prevalence in the age group 20 to 79 years were estimated to be 6.6% for the year 2010 which translates into 285 million people suffering from diabetes, according to international diabetes federation diabetes atlas. 20 The reasons for increasing prevalence are not clearly evident but changes in lifestyle and physical inactivity can be an important contributor.…”
Section: Original Research Articlementioning
confidence: 99%